Hindu Response to Dying and Death in the Time of COVID-19 - Bilimoria, Purushottama (Frontiers in Psychology, 2021)
We wake each morning to news on the glaring statistics of people infected by COVID-19 and others reportedly dying from complications thereto; the numbers are not receding in at least a number of countries across the world (barring a few that imposed strict lockdowns, testing and quarantining measures, such as Australia, Singapore, New Zealand and Vietnam). It is hard to imagine a moment such as this that most of us have lived through in our life-time; but it is a reality and public challenge that we can neither ignore nor look away from. In what follows I will explore perspectives on death from the Hindu tradition and the kinds of response—and solace or wisdom—afforded by the tradition to the angst and fears evoked by this pandemic situation. In concluding the discussion, I shall offer tentative reflections on how the Hindu perspective may be universalized, such as might invite conversations with therapists and care workers who may be seeking alternative resources to help expand the therapeutic space in more beneficent ways during the Covid-19 pandemic and its after-effects